The association between body mass index and molecular subtypes in endometrial carcinoma - DuPreez Smith; Eun Young Kang; Gregg S. Nelson; Cheng-Han Lee; Martin Köbel; Christa Aubrey (Elsevier, 2024)
Objective: This study aims to investigate the relationship between body mass index (BMI) and molecular subtypes of endometrial carcinoma using an immunohistochemistry (IHC)-based classification approach. Methods: We analyzed a consecutive series of endometrial cancer cases undergoing surgical staging in southern Alberta (2019-2021). Molecular classification was determined through IHC-based molecular typing, incorporating p53 and mismatch repair (MMR), and further characterized with the addition of ER and PR. BMI associations with molecular classification were assessed using t-tests. Hormone receptor status was further examined in a separate cohort of MMRd endometrial cancer patients undergoing surgical staging at Foothills Medical Centre (Alberta, Canada). Results: Among 289 cases, comprising various histological subtypes, the pNSMP subtype exhibited the highest average BMI (33.93 kg/m2) compared to the p53 abnormal subtype (30.40 kg/m2, p = 0.02). The MMRd subtype had an average BMI of 33.22 kg/m2. While there were no significant BMI differences between FIGO grade 1 and grade 2/3 tumours in the pNSMP or MMRd, a trend toward higher BMI in grade 1 tumours versus grade 2/3 tumours in the MMRd was observed (p = 0.13). A separate cohort of 53 MMRd endometrial carcinomas revealed that FIGO grade 1 tumours were associated with higher BMI (p < 0.05) and more frequent ER/PR expression compared to grade 2/3 tumours (p < 0.05). Conclusions: This study suggests an association between obesity and NSMP endometrial carcinoma. The relationship between BMI and low-grade MMRd endometrial carcinomas with increased ER/PR expression warrants further exploration.